Molecular epidemiology of Streptococcus uberis clinical mastitis in dairy herds: strain heterogeneity and transmission - Davies, P.L.; Archer, Simon C.; Emes, Richard D.; Bradley, Andrew J.; Leigh, J.A.; Green, Martin J. (American Society for Microbiology, 2016)
Multi Locus Sequence Typing was successfully completed on 494 isolates of S. uberis from clinical mastitis cases in a study of 52 commercial dairy herds over a 12 month period. In total, 195 sequence types (STs) were identified. S. uberis mastitis cases occurring in different cows within the same herd and attributed to a common ST were classified as 'potential transmission events' (PTE). Clinical cases attributed to 35 of the 195 STs identified in this study were classified PTE. PTE were identified in 63% of herds. PTE associated cases, which include the first recorded occurrence of that ST in that herd (Index case) and all persistent infections with that PTE ST represented 40% of all the clinical mastitis cases and occurred in 63% of herds. PTE associated cases accounted for over 50% of all S. uberis clinical mastitis cases in 33% of herds. Nine sequence types (ST 5, 6, 20, 22, 24, 35, 233, 361, and 512), eight of which grouped within a clonal complex (sharing at least four alleles), were statistically overrepresented (OVR STs). The findings indicate that 38% of all clinical mastitis cases and 63% of the potential transmission events attributed to S. uberis in dairy herds may be caused by the nine most prevalent strains. The findings suggest that to a small subset of sequence types are disproportionally important in the epidemiology of S. uberis mastitis in the UK with cow to cow transmission of S. uberis potentially occurring in the majority of UK herds and may be the most important route of infection in many herds.